Ultrasound-guided approach to surgery for nodal recurrence following lateral neck dissection for differentiated thyroid carcinoma. A single institution experience - Pacilli, Mario; Pavone, Giovanna; Quazzico, Andrea; Fersini, Alberto; Ambrosi, Antonio; Tartaglia, Nicola (Frontiers in Surgery, 2024)
Introduction: Total thyroidectomy (TT) and central neck dissection (CND) had a significant effect on the reduction of local recurrence compared with TT alone.Lateral Neck Dissection (LND) was performed in all the cases with therapeutic intent.The suspicion of nodal recurrence is provided by the appearance of one or more enlarged nodes in the central and/or laterocervical compartment during the follow up period. Methods: From January 2018 to November 2023, 16 patients at the University General Surgery unit of the Polyclinic of Foggia underwent reoperation due to nodal recurrence after previously undergoing total thyroidectomy with central and lateral cervical dissection. Results: All surgical interventions were approached with intraoperative ultrasound performed by the operating surgeon. In all cases, ultrasound identification of the suspicious lymph node led to histological confirmation of malignancy. In only two cases it was necessary to carry out an extemporaneous intraoperative histological examination. No complications were recorded during the operations. Conclusions: Surgical reintervention in patients with nodal recurrence is challenging and requires an assessment by members of the interdisciplinary team.The ideal method should be economically convenient, easy to practice, with a quick learning curve, easily reproducible, and safe for patients.Intraoperative, ultrasound-guided, is a safe and effective technique.It facilitates tumor localization and removal, especially in patients requiring re-operative neck surgery.